Awareness of Cervical Cancer Causes and Predeterminants of Likelihood to Screen Among Women in Haiti. Issue 1 (January 2017) - McCarthy, Schatzi H.; Walmer, Kathy A.; Boggan, Joel C.; Gichane, Margaret W.; Calo, William A.; Beauvais, Harry A.; Brewer, Noel T.
Abstract : Objectives: Cervical cancer is the leading cause of cancer deaths among women in Haiti. Given this high disease burden, we sought to better understand women's knowledge of its causes and the sociodemographic and health correlates of cervical cancer screening. Materials and Methods: Participants were 410 adult women presenting at clinics in Léogâne and Port-au-Prince, Haiti. We used bivariate and multivariate logic regression to identify correlates of Pap smear receipt. Results: Only 29% of respondents had heard of human papillomavirus (HPV), whereas 98% were aware of cervical cancer. Of those aware of cervical cancer, 12% believed that sexually transmitted infections (STIs) cause it, and only 4% identified HPV infection as the cause. Women with a previous sexually transmitted infection were more likely to have had Pap smear (34% vs 71%, odds ratio = 3.45; 95% CI = 1.57–7.59). Screening was also more likely among women who were older than the age of 39 years, better educated, and employed (all p < .05). Almost all women (97%) were willing to undergo cervical cancer screening. Conclusions: This sample of Haitian women had limited awareness of HPV and cervical cancer causes; but when provided with health information, they saw the benefits of cancer screening. Future initiatives should provide health education messages, with efforts targeting young and at-risk women. Abstract : Among Haitian women, there are large gaps in understanding of cervical cancer causes and prevention strategies, highlighting the need for increased public health information.